Diplopia due to Dacryops - Duman, Rahmi (Hindawi Publishing Corporation, 2013)
Dacryops is a lacrimal ductal cyst. It is known that it can cause globe displacement, motility restriction, and proptosis because of the mass effect. Diplopia due to dacryops has not been reported previously. Here, we present a 57-year-old man with binocular horizontal diplopia that occurred during left direction gaze due to dacryops.